DEVELOPMENT OF STUDENTS’ MEDIA LITERACY IN THE PROCESS OF CREATING SCHOOL MEDIA - Rybina, Ю.О. (Journal of Information Technologies in Education (ITE), 2017)
Nowadays, a rapid development of information and communication technologies enables combine a number of formats for presenting information into one communication unit. That is why the media (Internet especially) is not just tools for young generation for learning the modern world. Children enjoy in dealing with modern technologies. However not everyone has sufficient skills to objectively assess the true meaning of the information received. That is why children are more inclined for their mind to be manipulated and they are more inclined for blind imitating of attractive images. Owning to the above, the most priority-driven of modern education is the usage of information and communication technologies and media education for forming the skills of students' orientation in the information field and for forming the development of media immunity of the personality which makes the personality able to resist to the aggressive media space. Teachers face the challenge of introducing media education in middle and high schools.To implement the media education at the municipal institution regional specialized residential school “Giftedness” the pedagogical experiment was carried out there. The basis of the experiment is the generalized model of media literacy development for students that was used during for making and functioning the school newspaper «D.A.R-media». Theoretical aspects of the implementation of media education in the teaching and educational process of a specialized educational institution are considered in this study. A model for the development of the media literacy of students in the process of creating a school printed publication is proposed. Some results of research on the level of media literacy of students are highlighted and prospects for work on introducing media education of teachers and teachers are outlined.